Dramatic Experience The Poetics of Drama and the Early Modern Public Sphere(s) - Gvozdeva, Katja; Korneeva, Tatiana; Ospovat, Kirill (Drama and Theatre in Early Modern Europe, 2017)
The authors explore the convergence of dramatic theory, theatrical practice, and various modes of audience experience that contributed to the emergence of 'public sphere(s)' across early modern Europe - and in Asia.